IMPROVING SOME PARAMETERS OF ANTIBODY RESPONSE IN HORSES BY PROBIOTIC AGENTS AGAINST BACKGROUND USE OF MACROCYCLIC LACTONE ANTHELMINTIC - О. A. Mullagaliyeva; Ye. N. Zakrepina (Ветеринария сегодня)
Multiple researches demonstrate that both invasive diseases and use of anthelmintcs adversely affect horse immunity harming the gut flora. Macrocyclic lactone anthelmintics are proved to be highly effective agents but there is insufficient knowledge of their effect on the horse antibody immunity. The issue of immune system correction by the probiotic agents is also underreported. The paper demonstrates the results of the effect made by parascaridosis and strongylidosis invasion and deworming using the macrocyclic lactone drug on some parameters of antibody response in horses. Data on effect of probiotic Bioxymin horse on blood serum bacteriocidal and lysozyme activity were reported for the first time. The research was performed from December 2018 to January 2019. The results demonstrated that helminthic invasion and anthelmintic drug Univerm make depressive effect on some parameters of antibody response in horses. It also has an impact on the extensive efficacy of the anthelmintic agent. Probiotic Bioxymin horse makes a stimulating effect on the antibody response in horses.